The effect of the random and sequential exercise method on learning and accquiring the performance of the tennis forehand - Jabbar Abbas, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
The methods of modern scientific development have included various fields of life, and scientific applications have begun to take a wide space to create a developed and renewable world, investing all scientific methods and means in all areas of life, including the field of physical education, to reach the advanced scientific achievement. Hence the importance of the research to put practical steps in front of those interested in the educational process in general and tennis in particular to be a guide for teachers by recognizing the preference of any of the random and sequential exercise methods in learning and acquiring the performance of the forehand and knowing which of the methods are more influential in the learning process, which helps to facilitate In the process of learning and economy in effort, and the research problem lies, the researcher chooses some methods of scheduling the exercise and uses them to teach the skills of the game of tennis.